Penerapan Games Back To School Dengan Genre Education Fantasy Untuk Pelajar Usia Dini - Nur Mira Permatasari; Hermawan Arga Saputra; Farhandany Oktafarisky; Agung Widodo; Agustinus Bimo Gumelar; Maulana Rizqi (Jurnal Repositor, 2022)
One of the current trends is to incorporate technology into one's daily routine. If you have the right technology, you don't have to leave your house to have fun (enjoy and interact). Playing one of the built-in games on their smartphone or smartphone is the intended form of amusement. Even though there are a slew of other thrilling and tense games available to be played on a daily basis, the content in these games is mostly intended for entertainment purposes and offers very little in the way of real utility. This study examines how students and young children can benefit from instructional games (AUD). Players will have an easier time learning while having fun with this game because of the appealing manner in which it is packaged. The basic introduction to fruits and animals, numerical skills (Mathematics), Indonesian language and literacy skills, and spiritual talents are all part of the game's core elements, titled "Back to School" (Islam). In order to go on to the next grade, the player must correctly answer all ten questions in this game. There are also time constraints and playing possibilities given for each grade, which can help determine a student's overall score. The media platform used to create these games is based on HTML 5 and its build 2 component. Since the results of integrating Back to School games can be used across a wide range of operating systems, it is expected that the game will help stop young kids from abusing technology.